Detection of Microbial 16S rRNA Gene in the Serum of Patients With Gastric Cancer - Dong, Zhaogang; Chen, Bin; Pan, Hongwei; Wang, Ding; Liu, Min; Yang, Yongmei; Zou, Mingjin; Yang, Junjie; Xiao, Ke; Zhao, Rui; Zheng, Xin; Zhang, Lei; et al. (Frontiers in Oncology, 2019)
Aberrance in the blood bacterial microbiome has been identified and validated in several non-infectious diseases, including cancer. The occurrence and progression of gastric cancer has been found to be associated with alterations in the microbiome composition. However, the composition of the blood microbiome in patients with gastric cancer is not well characterized. To test this hypothesis, we conducted a case-control study to investigate the microbiota compositions in the serum of patients with gastric cancer. The serum microbiome was investigated in patients with gastric cancer, atypical hyperplasia, chronic gastritis, and in healthy control using 16S rRNA gene sequencing targeting the V1-V2 region. Our results revealed that the structure of the serum microbiome in gastric cancer was significantly different from all other groups, and alpha diversity decreased from the healthy control to patients with gastric cancer. The serum microbiome correlated significantly with tumor-node-metastasis (TNM) stage, lymphatic metastasis, tumor diameter, and invasion depth in gastric cancer. Three genera or species, namely, Acinetobacter, Bacteroides, Haemophilus parainfluenzae, were enriched in patients with gastric cancer, whereas Sphingomonas, Comamonas, and Pseudomonas stutzeri were enriched in the healthy control. Furthermore, the structure of serum microbiota differed between with gastric cancer lymphatic metastasis and non-lymphatic metastasis. As a pilot investigation to characterizing the serum microbiome in gastric cancer, our study provided a foundation for improving our understanding reading the role of microbiota in the pathogenesis of gastric cancer.